SANKSI PIDANA PELAKU PERDAGANGAN ORANG ONLINE MELALUI UNDANG-UNDANG NOMOR 11 TAHUN 2008 DAN TRANSAKSI ELEKTRONIK PASAL 27 AYAT 1 - Nurmayana, Suri; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
In light of "Law Number 11/2008 on Electronic Information and Transactions," this study addresses the criminal penalties for internet trafficking. Trafficking through online platforms is becoming more common as a result of the quick advancement of information technology, which presents significant difficulties for law enforcement. Examining the relevant legal provisions and the execution of criminal penalties in court-decided instances is the goal of this study. The following are issues with writing about the study: (1) Which sections of Law Number 11 of 2008 are pertinent to the criminal penalties for internet traffickers? (2) Based on previous court rulings, how are criminal penalties for traffickers using internet platforms being applied? It is intended that by thoroughly examining laws and writing, it will fulfill a function and demonstrate a commitment to the efficiency of law enforcement and the safety of human trafficking victims in the digital age. This study attempts to shed light on how well laws work to deter and punish those who engage in online human trafficking by using a normative juridical approach backed by a review of court rulings. The study aims to investigate how the law can best protect victims, especially in the increasingly complicated digital age. It is anticipated that the findings of this study will significantly aid in the creation of laws that are more efficient and sensitive to the difficulties posed by human trafficking in the digital sphere.Keywords: Online Pimps, EIT Law, Article 27 Paragra, Criminal Law, Online Human Trafficking, Law Enforcement Officers